The challenges of measuring social cohesion in public health research: A systematic review and ecometric meta-analysis - Moritz Oberndorfer; Thomas E. Dorner; Alastair H. Leyland; Igor Grabovac; Thomas Schober; Lukas Šramek; Marcel Bilger (Elsevier, 2022)
The relationship between social cohesion and health has been studied for decades. Yet, due to the contextual nature of this concept, measuring social cohesion remains challenging. Using a meta-analytical framework, this review's goal was to study the ecometric measurement properties of social cohesion in order to describe dissimilarities in its measurement as well as bring a new perspective on the empirical usefulness of the concept itself. To this end, we analysed if, and to what extent, contextual-level reliability and intersubjective agreement of 78 social cohesion measurements varied under different measurement conditions like measurement instrument, spatial unit, ecometric model specification, or region. We found consistent evidence for the contextual nature of social cohesion, however, most variation existed between individuals, not contexts. While contextual dependence in response behaviour was fairly insensitive to item choices, population size within chosen spatial units of social cohesion measurements mattered. Somewhat counterintuitively, using spatial units with, on average, fewer residents did not yield systematically superior ecometric properties. Instead, our results underline that precise theory about the relevant contextual units of causal relationships between social cohesion and health is vital and cannot be replaced by empirical analysis. Although adjustment for respondent's characteristics had only small effects on ecometric properties, potential pitfalls of this analytic strategy are discussed in this paper. Finally, acknowledging the sensitivity of measuring social cohesion, we derived recommendations for future studies investigating the effects of contextual-level social characteristics on health.